Student – Training Environment Interaction: Soft Skills Development within E-learning - Sergeyeva, Tetyana; Festeu, Dorin; Bronin, Sergiy; Turlakova, Natalya (My University, 2021)
The paper is intended to provide an insight into the practice of soft skills development in the process of students’ interaction with e-learning environment. The discussion calls upon the subject developers for a review of both the strategies of soft skills selection and the principles of transforming training courses into e-format. The paper is structured as follows: first, it reveals the ways of selecting a balanced optimal set of the university graduate’ soft skills on the basis of meta-level typology and individualization. Second, it identifies the principles of organizing efficient training activities aimed at the soft skills development that is based on modelling the existential (real life) situation of self-development. Third, it presents an exampleof the efficient training course transformation into e-learning format without losing its developmental capacity. It is worth noting that this paper provides an important source of information and creative ideas for e-learning courses aimed at soft skills development.
Keywords: soft skills; university Graduate Profile; e-learning; student-training environment interaction; developmental capacity